EFFORTS TO IMPROVE STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITY BY APPLYING THE GENERATIVE LEARNING TYPE COOPERATIVE MODEL - Antonius KAP Simbolon (Yayasan Nusantara Hasana Berdikari, 2025)
The purpose of this study was to determine whether there was an increase in students' mathematical problem solving abilities with the application of the cooperative model of the generative learning type. The type of research is quantitative research with a quasi-experimental method and the design used is pre-experimental. The research sample was students of SMP swasta Bina Sejahtera. Based on the results of the t-test, the t count value = 2.467 and the t-table value = 2.04227 with an α value = 0.05. Then the t count > t table is obtained, namely 2.467> 2.04227, so H0 is rejected. This means that the application of the generative learning model is effective based on the average posttest value of students' mathematical problem solving abilities in social arithmetic material.